El Código de Ética profesional del Contador Público en Perú y México. (2018)
Ethics in organizations implies a study of different variables, those linked to the behavior of the human being, as well as those related to the environment in which it operates. The research has a descriptive character and aims to develop a comparative study of the legal and accounting standards linked to the Code of Professional Ethics of the public accountant in Peru and Mexico to understand the likely incidence with corporate social responsibility. The study addresses the analy-sis of the legal and union regulations of the Public Accountant, with a general review of the Code issued by IFAC. The work is supported by a review of the relevant literature, based on concepts in which the application of ethical values is perceived by legal norms and accounting standards, linking their effects with the social responsibility that companies have as a result of the development of their operations.